Disc–jet coupling in the Terzan 5 neutron star X-ray binary EXO 1745−248. Issue 1 (29th April 2016) - Tetarenko, A. J.; Bahramian, A.; Sivakoff, G. R.; Tremou, E.; Linares, M.; Tudor, V.; Miller-Jones, J. C. A.; Heinke, C. O.; Chomiuk, L.; Strader, J.; Altamirano, D.; Degenaar, N.; et al.
Abstract: We present the results of Very Large Array, Australia Telescope Compact Array, and Swift X-ray Telescope observations of the 2015 outburst of the transient neutron star X-ray binary (NSXB), EXO 1745−248, located in the globular cluster Terzan 5. Combining (near-) simultaneous radio and X-ray measurements, we measure a correlation between the radio and X-ray luminosities of L_RL_X^β with β =1.68^+0.10_-0.09, linking the accretion flow (probed by X-ray luminosity) and the compact jet (probed by radio luminosity). While such a relationship has been studied in multiple black hole X-ray binaries (BHXBs), this work marks only the third NSXB with such a measurement. Constraints on this relationship in NSXBs are strongly needed, as comparing this correlation between different classes of XB systems is key in understanding the properties that affect the jet production process in accreting objects. Our best-fitting disc–jet coupling index for EXO 1745−248 is consistent with the measured correlation in NSXB 4U 1728−34 (β = 1.5 ± 0.2) but inconsistent with the correlation we fit using the most recent measurements from the literature of NSXB Aql X-1 (β =0.76^+0.14_-0.15 ). While a similar disc–jet coupling index appears to hold across multiple BHXBs in the hard accretion state, this does not appear to be the case with the three NSXBs measured so far. Additionally, the normalization of the EXO 1745−248 correlation is lower than the other two NSXBs, making it one of the most radio faint XBs ever detected in the hard state. We also report the detection of a type-I X-ray burst during this outburst, where the decay time-scale is consistent with hydrogen burning.